Analisis Usability Homepage Situs Web Perpustakaan Nasional RI Menggunakan Metode Think-Aloud - Indra Astuti; Wisnu Ananta Kusuma; Firman Ardiansyah (Perpustakaan IPB, 2016)
The study aims to usability analysis the National Library of Indonesia home page based the results of Paramjeet and Gupta research. The method used was think-aloud. In this method, one user was observed when doing the assignment and asked to express choices, feelings, or thoughts when testing the website. There are seven phases in this method, i.e 1) literature study of usability, usability testing and think- aloud, 2) self-evaluation of the home page of National Library of Indonesia website, conducted by comparing the results of Paramjeet and Gupta study, 3) determination of assessment parameters, 4) determination of the number and criteria of the respondents, 5) analysis of home page usability by the respondents, 6) analysis of the results, conducted based on the respondent transcripts, and 7) recommendations. There were ten respondents, with medium internet literacy skill. They expressed their thoughts and feelings when testing the home page. There were criteria used in the assessment :1) the main features consist of logo and name of organization, about us, contact us, and archive and archiving; 2)URL (Uniform Resources Locator); 3) window title; 4) date and time; 5) writing content; 6) navigation; 7) search; 8) graphic and animation.Based on the analysis, it shows that home page of the National Library of Indonesia website needs to be improved. The improvements needed are: the addition of about us feature on the main menu; contact us becomes part of about us in the main menu; the results of the archive and archiving is in the form of title, in order to facilitate the information retrieval; the moving boxes in the navigation are replaced with fixed boxes using different colors with the color news; the search is equipped with advanced search, and graphics and animation should also be improved not only as a home page ornament.Keywords :National Library of Indonesia, think-aloud, usability.